Análisis de los factores claves que han llevado a la India al éxito en la industria del software (Key factors analyses that take software industry of India to succeed) - Soto Espitia, Ilya María; Blanco Jiménez, Mónica; Galindo Mora, Juan Patricio; Osorio Calderón, Jesús (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. The purpose of this exploratory and descriptive research is to analyze theoretical perspective of the software industry of India, their model for development, and the variables that had an impact the productive as boosting of this industry. Currently is considering the leader of the software industry. We identify which are the factors that affect this development. Then we will analyze if these factors are suitable to implement in Mexico in the software industry to increase the competitiveness. Software industry is growing fast and also impact all economy sectors because implies development and technological advance. This reasons are the cause why is important to analyze software industry. This article will talk about five factors that we select that have an effect in the software industry of India, and these factors are: talent development, promotion of professional education, collaboration between industry, government and universities, technological park increase, intellectual property protection.